Patterns of Providing Complementary Food with Incidents of Stunting in Toddlers in Kupang City, Ages 6-24 Months - Astuti Nur; Anita Ch Sembiring; Maria Helena Dua Nita (Sarana Ilmu Indonesia (salnesia), 2023)
The province of East Nusa Tenggara has a high rate of malnutrition, particularly stunting. The development of toddlers is significantly influenced by complementary foods. Inappropriate supplementation of food may increase the risk of stunting. The purpose of this study is to ascertain how supplemental feeding practices affect the prevalence of stunting in children in Kupang City between the ages of 6 and 24 months. An analytical survey with a cross-sectional design was employed in this kind of study. The population was all toddlers in Kupang City, with a total of 25.266 children. A multistage random sample technique was used to choose 394 children between the ages of 6 and 24 months to participate in the study. Chi-square test was utilized in the data analysis. The results showed that there was a significant relationship between the number of complementary foods (p-value=0,001, OR 2,691), the texture of complementary foods (p-value=0,025, OR 1,907), and the frequency of complementary foods (p-value=0,000, OR 3,945) and the incidence of stunting among children aged 6–24 months in Kupang City.